Optimal bi-criterion planning of rescue and evacuation operations for marine accidents using an iterative scheduling algorithm - Ng, Chi To; Cheng, T. C. E.; Levner, Eugene; Kriheli, Boris (Annals of operations research, 2021)
We consider the problem of real-life evacuation of people at sea. The primary disaster response goal is to minimize the time to save all the people during the evacuation operation, taking into account different groups at risk (children, women, seniors etc.) and the evacuation processing time (including the routing time), subject to a budget constraint. There are different evacuation tools (e.g., lifeboats, salvage ships, sea robots, helicopters etc.) for rescuing groups at risk to some safe points (e.g., hospitals, other ships, police offices etc.). The evacuation processing time of a group at risk depends on the group and the evacuation tool used. The secondary goal is to minimize the cost among all the alternative optimal solutions for the primary goal. We present a new mathematical rescue-evacuation model and design a fast solution method for real-time emergency response for different population groups and different evacuation tools, based on iterative utilization of a modification of the scheduling algorithm introduced by Leung and Ng (Eur J Oper Res 260:507–513, 2017).